Prophylactic levofloxacin in cancer chemotherapy: a randomized controlled study - Peters, Jyotika; Badyal, Dinesh K.; John, Joseph M. (International Journal of Research in Medical Sciences, 2018)
Background: The patients on cancer chemotherapy are at substantial risk of developing febrile episodes, bacteremia and infection related mortalities, yet the prophylactic use of antimicrobials continues to be a controversial issue. Hence, this study was designed to study the effect of antimicrobial prophylaxis in cancer chemotherapy. Methods: The patients receiving the cancer chemotherapy were randomly divided into two groups. Group A patients received cancer chemotherapy and no prophylactic antimicrobials. Group B patients were given prophylactic levofloxacin with each cancer chemotherapy cycle. Patients were evaluated for febrile episodes, documented infections and hospitalizations. The Eastern Cooperative Oncology Group (ECOG) performance grade and culture sensitivity reports were also recorded. Results: Demographic profile of patients was comparable in both groups. Absolute neutrophil count at 6 weeks was significantly higher with levofloxacin prophylaxis. Levofloxacin prophylaxis led to 92% reduction in risk of having neutropenia in first cycle, 78% reduction in clinically documented febrile episodes during the first chemotherapy cycle (36 % vs 8%, 95% confidence interval 0.08 to 0.56, p<0.001), 88% reduction in risk of developing infections, 63% reduction in risk of hospitalization and 30% decrease in average cost of treatment per patient per day (₹1269.80±220.32 vs. ₹372.21±99.23, p<0.01) as compared to control group. All documented infections were from gram negative bacteria, E. coli being the commonest. Conclusions: Antimicrobial prophylaxis with levofloxacin is beneficial to patients receiving cancer chemotherapy as it decreases the morbidity, in terms of febrile episodes, neutropenia, infections, hospitalizations and it also reduces the cost of overall treatment.